Predicting the fraud volume in personal computer using different web browsers - Z, Nuha; Shah, Asadullah (Science International, 2017)
Online banking had grown tremendously in the recent yeats due to the vast development of internet applications on both computer and handheld devices. However, this advancement is faced by equally growing fraud attacks over the last decade. Customers awareness and vender awareness are considered important factors in the study of fraud attacked volume increase. Stringent security standards and multiple defensive security lines have proposed to reduce the fraud attack cases. Neverthless, fraud attacks cases are showing a relentless increase in the past decade. This paper presents fraud attack prediction from a new perspective. Adaptive neuro-fuzzy inference system (INFIS) was utilised for the data collected in the past decades and then used to predict the effect of internet usage rate on the fraud attack volume of different age groups as well as the total fraud volume in the future. Seven different scenarios in this study are considered to be addressing the effect of different web browsers on the fraud volume. Results show that fraud volume would increase with the increasing of using Mozilla, Firefox, Opera, Safari and Chrome and would decrease with the increasing of internet explorer and Netscap